Morphological, morphometric and stereological study of submandibular glands in rats with lesion of the anteroventrai region of the third ventricle (AV3V) - Renzi, A. [UNESP]; Lopes, R. A. [UNESP]; Sala, M. A. [UNESP]; Camargo, L. A.A. [UNESP]; Menani, J. V. [UNESP]; Saad, W. A. [UNESP]; Campos, G. M. [UNESP] (Elsevier, 1990)
Lesions of the antero-ventral region of the third ventricle induce in the rat submandibular gland parenchyma, atrophy through vascular ischemia, and simultaneously increased fibrosis of the connective tissue, probably by alteration of the pituitary gonadotropins (FSH, LH), thyrotrophic hormone (TSH), growth hormone and probably insulin levels. © 1990, VEB Gustav Fischer Verlag Jena. All rights reserved.
Keywords: anteroventral region, 3rd ventricle; cephalic reflexes; gonadotropins, pituitary; growth hormone; hypothalamic lesion; insulin; submandibular glands; thyrotrophic hormone; ventricle, third